Cargoes of exosomes function as potential biomarkers for Mycobacterium tuberculosis infection - Wang, Nan; Yao, Yongliang; Qian, Yingfen; Qiu, Dewen; Cao, Hui; Xiang, Huayuan; Wang, Jianjun (Frontiers in Immunology, 2023)
Exosomes as double-membrane vesicles contain various contents of lipids, proteins, mRNAs and non-coding RNAs, and involve in multiple physiological processes, for instance intercellular communication and immunomodulation. Currently, numerous studies found that the components of exosomal proteins, nucleic acids or lipids released from host cells are altered following infection with Mycobacterium tuberculosis.Exosomal contents provide excellent biomarkers for the auxiliary diagnosis, efficacy evaluation, and prognosis of tuberculosis. This study aimed to review the current literatures detailing the functions of exosomes in the procedure of M. tuberculosis infection, and determine the potential values of exosomes as biomarkers to assist in the diagnosis and monitoring of tuberculosis.